The Use of Information and Communication Technology in English Foreign Language Learning - Otieno, Polycarp (International Journal of Linguistics, 2023)
Purpose: The purpose of this study is to investigate the use of ICT in English foreign language learning. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the use of ICT in English foreign language learning. Preliminary empirical review reveals that ICT presents a powerful learning environment for learners in the classroom. Many countries make investments in ICT integration as ICT is viewed as an effective tool for renewing educational practice in any field. Because teachers are the main characters to employ ICT in educational contexts, they should be trained in how ICT can be integrated into the teaching process. Unique Contribution to Theory, Practice and Policy: The Cognitive Load theory, the Interactionist theory and the Constructivist theory may be used to anchor future studies in the use of ICT in English foreign language learning. This study will provide some insights to instructors, policymakers and other relevant stakeholders in the integration of ICT in the teaching and learning of English as a foreign language to produce better results.